Práticas e vivencias dos estágios supervisionado na gestão, na educação infantil e nos anos iniciais dos ensino fundamental em duas escolas públicas de Juruá/ AM - Lima, Mário Bezerra de (Brasil, 2024)
This work aims to describe and analyze the experiences obtained throughout the internship phases that make up the trajectory of the Pedagogy course, relating these experiences with the reflections present in the training memorial. Reflect on personal and professional development during the stages of training, based on the training memorial. To analyze the practical experiences lived during the internship phases of the pedagogy course and its contributions to teacher training. Relate the internship experiences with the theories and reflections developed throughout the pedagogy course. Regarding Early Childhood Education, the intern is involved in a playful and dynamic environment in early childhood education, where all activities offer opportunities for discovery and learning. In their records, the importance of understanding the characteristics of each child is highlighted and they recognize that playing is the main language through which the little ones express their feelings and build their knowledge. The fact that educators must play the role of mediators, creating a favorable environment that encourages curiosity and fosters social and emotional development is emphasized. In the Early Years of Elementary School, these experiences show the importance of a pedagogical approach that values creativity and individual expression. In the Education Management Internship focuses on the importance of establishing strong bonds between school and family, cultivated with respect and empathy. And all these learnings were possible through direct observations with the school environment and all the people involved in this scenario. It is evidently proven that supervised internships are fundamental to provide rich learning to future teachers who in a certain way will rebuild, innovate, improve themselves, from each experience lived in the internships, so that each knowledge learned is in fact applied in the practice of this professional efficiently.